Serum FGF21 Levels Are Increased in Obesity and Are Independently Associated With the Metabolic Syndrome in Humans - Xinmei Zhang; Dennis C.Y. Yeung; Michal Karpíšek; David Stejskal; Zhiguang Zhou; Feng Liu; Rachel L.C. Wong; Wing‐Sun Chow; Annette W.K. Tso; Karen S.L. Lam; Aimin Xu (2008)
OBJECTIVE— Fibroblast growth factor 21 (FGF21) is a metabolic regulator with multiple beneficial effects on glucose homeostasis and insulin sensitivity in animal models. This study aimed to investigate the relationship between its serum levels and various cardiometabolic parameters in humans. RESEARCH DESIGN AND METHODS— A newly developed immunoassay was used to measure serum FGF21 levels in 232 Chinese subjects recruited from our previous cross-sectional studies. The mRNA expression levels of FGF21 in the liver and adipose tissues were quantified by real-time PCR. RESULTS— Serum FGF21 levels in overweight/obese subjects were significantly higher than in lean individuals. Serum FGF21 correlated positively with adiposity, fasting insulin, and triglycerides but negatively with HDL cholesterol, after adjusting for age and BMI. Logistic regression analysis demonstrated an independent association between serum FGF21 and the metabolic syndrome. Furthermore, the increased risk of the metabolic syndrome associated with high serum FGF21 was over and above the effects of individual components of the metabolic syndrome. Our in vitro study detected a differentiation-dependent expression of FGF21 in 3T3-L1 adipocytes and human adipocytes. In db/db obese mice, FGF21 mRNA expression was markedly increased in both the liver and adipose tissue compared with that in their lean littermates. Furthermore, FGF21 expression in subcutaneous fat correlated well with its circulating concentrations in humans. CONCLUSIONS— FGF21 is a novel adipokine associated with obesity-related metabolic complications in humans. The paradoxical increase of serum FGF21 in obese individuals, which may be explained by a compensatory response or resistance to FGF21, warrants further investigation.